Physiological, anthropometric and athletic performance adaptations from completing a 1-month pre-season period. A two-year longitudinal study in female collegiate soccer players - Perrotta, Andrew S.; Day, Brent D.; Correa, Camila J.; Scott, Anika J.; Ramos, Jennifer; Gnatiuk, Elizabeth A.; Warburton, Darren E. R. (Frontiers in Sports and Active Living, 2024)
Introduction Collegiate coaches and integrative support staff often utilize pre-season as a brief and intense training period to prepare athletes technically, tactically, and physiologically, to meet the demands of competition during a soccer season. This study sought to examine the dose-response from performing on-field soccer activities during a four-week pre-season period in female collegiate soccer players, and if the magnitude in response was associated with accumulated exercise stress. Methods A total of twenty-seven healthy female soccer players training as part of a collegiate soccer program volunteered to participate in this two-year longitudinal study. Data collection commenced prior to the start of each pre-season period, at the beginning of August, and was completed at the beginning of September, when pre-season ended. Data collection periods were separated by a 31-day period. Indices of cardiovascular function, anthropometry, and athletic performance were examined during each data collection period. Internal and external measures of accumulated exercise stress were recorded using the Polar Team Pro® system. Results When comparing the beginning to the end of pre-season, significant improvements were observed in body fat (%) [24.2 ± 6.0 “vs.” 23.3 ± 5.6, p = 0.001], heart rate variability (rMSSD) [51.8 ± 25.1 “vs.” 67.9 ± 34.6 ms, p = 0.002], resting heart (bpm) [73.8 ± 12.1 “vs.” 64.3 ± 8.8, p = 0.001] and cardiorespiratory performance (YoYo IRTL-1) [925.8 ± 272.8 “vs.” 1,062.6 ± 223.3 m, p = 0.001]. Significant reductions in musculoskeletal performance were observed through vertical jump height (cm) [24.9 ± 23.7, p = 0.04]. Change in the end of pre-season body weight (kg) was significantly associated with accumulated accelerations and decelerations [r ≥ 0.49, p = 0.01]. End of pre-season change in cardiorespiratory performance was significantly associated with both accumulated training load (au) and TRIMP (au) [r ≥ 0.63, p = 0.01]. Discussion In conclusion, performing a four-week pre-season period, involving only on-field training, can promote positive and significant adaptations in anthropometry, cardiovascular function, and athletic performance measures in female collegiate soccer players. The magnitudes of these adaptations were associated with both internal and external measures of accumulated exercise stress.